Effect of integrated nutrient management on productivity and profitability of mustard [Brassica juncea (L.) Czern & Coss] - Pradeep Dhaka,; Devi Lal Dhaker,; O. P. Sharma,; Manjeet Dhaka, (Annals of Agricultural Research, 2024)
A field experiment was undertaken during rabi season of 2022-23 at Research Farm, School of Agriculture, Suresh Gyan Vihar University, Jaipurto study the effect of integrated nutrient management on yield and economics of mustard [Brassica juncea (L.) Czern & Coss]. The experiment was taken in randomized block design with three replications assigning eight treatment combinations of inorganic fertilizers and organic fertilizers. Results showed that the yield attributes, yield and economics of mustard was significantly in creased due to different integrated nutrient management treatments as compared to control. The maximum number of siliquae plant-1, number of seeds siliqua-1, seed yield, stover yield, biological yield, net returns and B:C ratio of mustard was obtained by application of 100% RDF(T1 ) which was closely followed by 50% RDF + vermicompost at 2.0 t ha-1 (T5 ) and 50% RDF + poultry manure at 2.5 t ha-1(T7 ).